ABSCISIC ACID INSENSITIVE5 Interacts With RIBOSOMAL S6 KINASE2 to Mediate ABA Responses During Seedling Growth in Arabidopsis - Li, Linxuan; Zhu, Tingting; Song, Yun; Feng, Li; Farag, Essam Ali Hassan; Ren, Maozhi (Frontiers in Plant Science, 2021)
ABSCISIC ACID INSENSITIVE5 (ABI5) is an important regulator of abscisic acid (ABA) signaling pathway involved in regulating seed germination and postgerminative growth in Arabidopsis, which integrates various phytohormone pathways to balance plant growth and stress responses. However, the transcriptional regulatory mechanisms underlying ABI5 and its interacting proteins remain largely unknown. Here, we found that inhibition of AtTOR could increase ABA content by up-regulating the expression levels of ABA biosynthesis-related genes, and thus activated the expression of ABA-responsive genes. Pharmacological assay showed that abi5-1 mutant was insensitive to TOR inhibitor AZD8055, whereas AtABI5 overexpression lines were hypersensitive to AZD8055 in Arabidopsis. Biochemical interaction assays demonstrated that ABI5 physically interacted with the RIBOSOMAL S6 KINASE2 (S6K2) protein in plant cell. S6K2 positively regulated ABA responses during seedling growth and upregulated ABA-responsive genes expression. Furthermore, genetic and physiological analysis indicated that AtS6K2 overexpression lines enhanced resistance to drought treatment while AtS6K2 interference lines were sensitive to drought. These results indicated that AtABI5 interacted with AtS6K2 to positively modulate ABA responses during seedling growth and shed light on a underlying mechanism of the crosstalk between TOR and ABA signaling pathways in modulating seedling growth in Arabidopsis.